Designing strong inducible synthetic promoters in yeasts - Masahiro Tominaga; Yoko Shima; Kenta Nozaki; Yoichiro Ito; Masataka Someda; Yuji Shoya; Noritaka Hashii; Chihiro Obata; Miho Matsumoto-Kitano; Kohei Suematsu; Tadashi Matsukawa; Keita Hosoya; et al. (Nature Communications)
Abstract Inducible promoters are essential for precise control of target gene expression in synthetic biological systems. However, engineering eukaryotic promoters is often more challenging than engineering prokaryotic promoters due to their greater mechanistic complexity. In this study, we describe a simple and reliable approach for constructing strongly inducible synthetic promoters with minimum leakiness in yeasts. The results indicate that the leakiness of yeast-inducible synthetic promoters is primarily the result of cryptic transcriptional activation of heterologous sequences that may be avoided by appropriate insulation and operator mutagenesis. Our promoter design approach has successfully generated robust, inducible promoters that achieve a > 103-fold induction in reporter gene expression. The utility of these promoters is demonstrated by using them to produce various biologics with titers up to 2 g/L, including antigens designed to raise specific antibodies against a SARS-CoV-2 omicron variant through chicken immunization.